A cross‐sectional survey to assess the knowledge, attitudes and common barriers to the reporting of adverse drug reactions by the general public in Malaysia. (4th August 2018) - Mohammad, Arief; Bheemavarapu, Harika; Khan, Muhammad Umair; Khan, Anam; Ahmad, Akram; Hassali, Mohamed Azmi Ahmed; Blebil, Ali Qais
Abstract: Background: An adverse drug reaction (ADR) is a noxious and unintended response to a drug which occurs at a normal therapeutic dose. Most non‐dose related ADRs remain unpredicted and increase morbidity and mortality. Despite the introduction, in Malaysia, of a spontaneous ADR reporting system, a sizable number of ADR cases remain under‐reported. Objective: To assess the knowledge and attitudes of consumers toward ADRs, and to determine the common barriers toward reporting an ADR in Malaysia. Methods: A descriptive, cross‐sectional study was carried out for a period of 3 months in Cheras, Malaysia. The data were collected by a self‐administered questionnaire consisting of four sections. Results: Among the 400 respondents, 144 (36%) were male and 256 (64%) were female. The majority of the respondents were Chinese (n = 227, 57%) and 54.5% of them were treated with a medication in the past year. About 60.75% (n = 243) of participants reflected inadequate knowledge when asked what is an ADR. A sizable number of the participants (n = 333, 83%) were unaware of the ADR reporting centre in Malaysia, and about 86% (n = 344) stated that they were not aware of the ADR reporting procedure. The main reasons as considered by the participants for under‐reporting an ADR were inadequate knowledge regarding the drugs (n = 395, 87.4%), unawareness of the reporting procedure (n = 320, 80%), lack of an online process to report an ADR (n = 299, 75%), and other significant factors such as lack of time, incentives, proper advertisement, motivation and uncertainty of an ADR, with percentages of 62 (n = 248), 50 (n = 201), 80.5 (n = 322), 78 (n = 312) and 83 (n = 331) respectively. Conclusion: As most of the participants were still unaware about the availability of the ConSERF form which was introduced by the National Pharmaceutical Regulatory Agency (NPRA) in 2015, healthcare providers, as well as the Malaysian Adverse Drug Reactions Advisory Committee, need to improve public education regarding this system. The public awareness about the availability of various methods of the ADR reporting can help improve ADR reporting by consumers.